Kajian Kepadatan, Distribusi, dan Habitat Burung Paruh Bengkok di Kawasan Hutan Lindung Praimbana Lakatang, Kabupaten Sumba Timur - March Cahya Maru Lobo; Maria M. E. Purnama; Oki Hidayat (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2025)
The existence of parrot species in Sumba Island is unique and attractive, but their population is decreasing due to illegal hunting and trade. This research was conducted in Luku Melolo Forest, Praimbana Lakatang Protected Area, using IPA (Index Ponctualle de’Abondance), Line Transect, Vegetation Analysis, and habitat observation methods. Results showed that the highest population density was found in Orange-crested Cockatoo (1.44 ind/ha), while other species such as Red-cheeked Parrot, Eclectus Parrot, and Orange Parrot had 0.2 ind/ha each. The distribution pattern of all four species was random. The dominant vegetation was Bidara (Zizipus mauritiana L.) with the highest INP value, while Bamboo (Bambusoideae) had the lowest INP. The Shannon-Wiener diversity index (H’=2.66) indicated a medium level of species diversity. This study provides essential insights for the conservation of parrots in East Sumba